2016
DOI: 10.1002/chem.201603048
|View full text |Cite
|
Sign up to set email alerts
|

Structure Determination of an AgI‐Mediated Cytosine–Cytosine Base Pair within DNA Duplex in Solution with 1H/15N/109Ag NMR Spectroscopy

Abstract: The structure of an Ag(I) -mediated cytosine-cytosine base pair, C-Ag(I) -C, was determined with NMR spectroscopy in solution. The observation of 1-bond (15) N-(109) Ag J-coupling ((1) J((15) N,(109) Ag): 83 and 84 Hz) recorded within the C-Ag(I) -C base pair evidenced the N3-Ag(I) -N3 linkage in C-Ag(I) -C. The triplet resonances of the N4 atoms in C-Ag(I) -C demonstrated that each exocyclic N4 atom exists as an amino group (-NH2 ), and any isomerization and/or N4-Ag(I) bonding can be excluded. The 3D structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 63 publications
(43 reference statements)
1
61
0
Order By: Relevance
“…Furthermore, the thymine‐Hg II ‐thymine in a duplex of a B‐form double helix, has been also characterized by NMR spectroscopy . Finally, the crystal structure of a silver(I)–RNA hybrid duplex containing Watson–Crick like cytosine‐silver(I)‐cytosine metallo base‐pairs and a related NMR structural study in solution of a DNA duplex comprising cytosine‐Ag I ‐cytosine base pairs have been recently published, paving the way to the structure‐based design of nucleic acid‐based nanodevices. Despite these advances, the number of X‐ray structures of metal‐mediated base‐pairs models or metal complexes with nucleic acids remains limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the thymine‐Hg II ‐thymine in a duplex of a B‐form double helix, has been also characterized by NMR spectroscopy . Finally, the crystal structure of a silver(I)–RNA hybrid duplex containing Watson–Crick like cytosine‐silver(I)‐cytosine metallo base‐pairs and a related NMR structural study in solution of a DNA duplex comprising cytosine‐Ag I ‐cytosine base pairs have been recently published, paving the way to the structure‐based design of nucleic acid‐based nanodevices. Despite these advances, the number of X‐ray structures of metal‐mediated base‐pairs models or metal complexes with nucleic acids remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these advances, the number of X‐ray structures of metal‐mediated base‐pairs models or metal complexes with nucleic acids remains limited. For pyrimidinic bases, the complexes are restricted to Ag I , Hg II , and Pt II . Finally, for Au III there is only one example with RNA in which the metal links a guanine to a cytosine …”
Section: Introductionmentioning
confidence: 99%
“…In this study, we focused on the effect of sugar conformation on MMBPs in DNA/DNA duplexes, and we investigated the application of 2′,4′‐BNA/LNA in MMBPs (Scheme ). We expected that 2′,4′‐BNA/LNA would improve the thermal stability of the duplex containing C‐Ag I ‐C because the sugar conformation in C‐Ag I ‐C is predominantly that of N‐type ,. As expected, 2′,4′‐BNA/LNA with 5‐methylcytosine (C L ) effectively stabilized the Ag I ‐mediated base pair with C and improved the duplex‐forming ability in DNA/DNA duplexes, relative to the unmodified structure.…”
Section: Introductionmentioning
confidence: 82%
“…Such duplexes containing MMBPs do not induce large conformational changes. These studies have reported that the predominant sugar conformations in C‐Ag I ‐C are of N‐type in DNA/DNA and RNA/RNA . However, the sugar in T‐Hg II ‐T may not exist in the preferred conformation .…”
Section: Introductionmentioning
confidence: 99%
“…The CD spectra further indicate that the duplex adopts a B‐type conformation and that the formation of the ϵ A‐Ag I ‐C base pair does not significantly alter that conformation. An inadvertent formation of C‐Ag I ‐C base pairs within oligonucleotide ODN2 as a cause of the observations described in Figure can be ruled out (the Supporting Information, Figure S1).…”
Section: Methodsmentioning
confidence: 92%